Club Cell Protein, CC10, Attenuates Acute Respiratory Distress Syndrome Induced by Smoke Inhalation. Issue 3 (March 2020) - Lopez, Ernesto; Fujiwara, Osamu; Nelson, Christina; Winn, Melissa E.; Clayton, Richard S.; Cox, Robert A.; Hawkins, Hal K.; Andersen, Clark R.; Wade, Charles E.; Hariprakasha, Humcha; Prough, Donald S.; Pilon, Aprile L.; et al.
ABSTRACT: Objectives: To evaluate the dose effects of Recombinant human Club cell 10-kDa protein (rhCC10) on lung function in a well-characterized ovine model of acute respiratory distress syndrome (ARDS) induced by smoke inhalation injury (SII); specifically, the potential of rhCC10 protein to control the inflammatory response and protect pulmonary tissue and function following SII. Design: Randomized, controlled, prospective, and large animal translational studies. Setting: University large animal intensive care unit. Subjects: Thirty-six adult female sheep were surgically prepared and allocated into five groups (Sham (no SII), n = 6; 1 mg/kg/d CC10, n = 8; 3 mg/kg/d CC10, n = 7; 10 mg/kg/d CC10, n = 8; Control SII, n = 7). Interventions: All groups except the sham group were subjected to SII with cooled cotton smoke. Then, the animals were placed on a ventilator, treated with 1, 3, and 10 mg/kg/d of intravenous rhCC10 or vehicle, divided evenly into two administrations per day every 12 h, fluid resuscitated, and monitored for 48 h in a conscious state. Measurements and main results: The group treated with 10 mg/kg/d rhCC10 attenuated changes in the following variables: PaO2 /FiO2 ratio, oxygenation index, and peak inspiratory pressure; neutrophil content in the airway and myeloperoxidase levels; obstruction of the large and small airways; systemic leakage of fluid and proteins, and pulmonary edema. Conclusions: In this study, high-dose rhCC10 significantly attenuated ARDS progression and lung dysfunction and significantly reduced systemic extravasation of fluid and proteins, normalizing fluid balance. Based on these results, rhCC10 may be considered a novel therapeutic option for the treatment of SII-induced ARDS. Abstract : Supplemental Digital Content is available in the text